1999
DOI: 10.1016/s0002-9440(10)65504-6
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of the INK4A Gene Occur in Malignant Peripheral Nerve Sheath Tumors but not in Neurofibromas

Abstract: The INK4 family of cyclin-dependent kinase inhibitors (CKIs) includes p16, 1 p15, 2 p18, 3 and p19. 4 INK4A gene, also known as CDKN2A gene, is located on the short arm of chromosome 9 (9p21), 5 and its coding sequence consists of three exons with two alternative first exons, E1␣ and E1␤. Splicing of E1␣ with exons 2 and 3 encodes a 1.5845-kd protein known as p16. p16 complexes with and inactivates cyclin-dependent kinases 4 (Cdk4) and 6 (Cdk6), thus preventing phosphorylation of the retinoblastoma protein (pR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 27 publications
4
98
0
Order By: Relevance
“…These tumors overexpress p16 Ink4a , and show senescence-associated acidic b-galactosidase activity, BRAF mutations and growth arrest, with null or very low proliferative activity (Romagosa et al, 2009;Serrano et al, 2010). Moreover, the malignant counterparts of both tumors, melanoma and malignant peripheral nerve sheath tumor, are immunohistochemically negative for p16 Ink4a (Figure 2) (Sabah et al, 2006), and loss of p16 Ink4a has been involved in the development of both types of neoplasms (Kourea et al, 1999;Nielsen et al, 1999;Perrone et al, 2003;Sabah et al, 2006). Therefore, some benign tumors overexpress p16 Ink4a and this overexpression seems to control proliferation in response to oncogenic stimuli, protecting the cell from malignant transformation.…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 99%
“…These tumors overexpress p16 Ink4a , and show senescence-associated acidic b-galactosidase activity, BRAF mutations and growth arrest, with null or very low proliferative activity (Romagosa et al, 2009;Serrano et al, 2010). Moreover, the malignant counterparts of both tumors, melanoma and malignant peripheral nerve sheath tumor, are immunohistochemically negative for p16 Ink4a (Figure 2) (Sabah et al, 2006), and loss of p16 Ink4a has been involved in the development of both types of neoplasms (Kourea et al, 1999;Nielsen et al, 1999;Perrone et al, 2003;Sabah et al, 2006). Therefore, some benign tumors overexpress p16 Ink4a and this overexpression seems to control proliferation in response to oncogenic stimuli, protecting the cell from malignant transformation.…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 99%
“…Mutations that affect the p16 INK4A -cyclin D1-cyclin-dependent kinase (CDK)4-Retinoblastoma (Rb) and p19 ARF -Mdm2-p53 cell cycle regulatory pathways were among the first linked to MPNST pathogenesis. CDKN2A mutations occur in up to 50% of MPNSTs 44,45 and are especially deleterious because they dysregulate both of these cell cycle regulatory pathways. This is because CDKN2A encodes both p16 INK4A , which inhibits CDK4 and CDK6, and p19 ARF , a protein that inhibits Mdm2, an E3 ubiquitin-protein ligase which tags p53 for proteasomal degradation.…”
Section: Genomic Abnormalities Mediating Neurofibroma-mpnst Progressionmentioning
confidence: 99%
“…10,11 Currently, our understanding of the biological mechanisms underlying NF1 tumourigenesis is rather limited, although recent studies in mouse have (i) confirmed a direct role for the tumour microenvironment and (ii) identified skin-derived precursor cells as the cell of origin for cutaneous neurofibromas. 12 In studies of NF1 patients, somatic mutations affecting a number of other tumour suppressor genes, including TP53, CDKN2A and RB1 (variously involved in cell cycle regulation, DNA synthesis and apoptosis), have also been identified in MPNSTs, [13][14][15][16][17] PNFs 18,19 and those cutaneous neurofibromas that have been removed from NF1 patients who carry a particularly high tumour burden. 20 It is currently unclear (i) why some types of neurofibroma are present from birth, whereas others develop only during adolescence, (ii) what initiates neurofibroma growth and (iii) what determines the number of tumours that develop in a given individual.…”
Section: Introductionmentioning
confidence: 99%